2009
DOI: 10.1016/j.peptides.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two novel polyfunctional mastoparan peptides from the venom of the social wasp Polybia paulista

Abstract: Hymenoptera venoms are complex mixtures of biochemically and pharmacologically active components such as biogenic amines, peptides and proteins. Polycationic peptides generally constitute the largest group of Hymenoptera venom toxins, and the mastoparans constitute the most abundant and important class of peptides in the venom of social wasps. These toxins are responsible for histamine release from mast cells, serotonin from platelets, and catecholamines and adenylic acids from adrenal chromafin cells. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 46 publications
0
56
1
2
Order By: Relevance
“…Mast cell lysis was assayed by measuring the leakage of lactate dehydrogenase (LDH) from the mast cell cytoplasm; the LDH assay was performed as previously described [23]. The cells utilized in this assay were the same as those used in mast cell degranulation assay, described above.…”
Section: Mast Cell Lysismentioning
confidence: 99%
“…Mast cell lysis was assayed by measuring the leakage of lactate dehydrogenase (LDH) from the mast cell cytoplasm; the LDH assay was performed as previously described [23]. The cells utilized in this assay were the same as those used in mast cell degranulation assay, described above.…”
Section: Mast Cell Lysismentioning
confidence: 99%
“…[Lys 10 , Leu 13 ] mastoparan, another tetradecapeptide from wasp venom toxin, has been found to have the same mast cell activation role as mastoparan, and it is a much better tool for study of the mechanism of mast cell degranulation and intracellular signal transmission (26). What is more, it has been discovered recently that two novel mastoparan peptides (Polybia-MP-II and -III) from the venom of the neotropical social wasp Polybia paulista can also trigger activation of mast cells (31).…”
Section: By Basic Secretagoguesmentioning
confidence: 99%
“…Potential cancer biomarker (Slaby et al 2009;van de Sande et al 2006) Is the target of various anticancer drugs and so it could be used as a potential target for therapy (Tuynder et al 2004 Mast cell degranulation (Hirai et al 1979 Activation of G-protein-mediated mechanisms (Higashijima et al 1988;Perianin and Snyderman 1989;Ozaki et al 1990) Inhibition of calmodulin-mediated mechanisms (Wheeler-Jones et al 1992;Joyce-Brady et al 1991) Stimulation of phospholipases A 2 and C (Wallace and Carter 1989; Perianin and Snyderman 1989) Stimulation or inhibition of cation-specific channels (Glavinovic et al 1992) Hemolytic activity (Souza et al 2009)…”
Section: Venommentioning
confidence: 99%
“…The encapsulated mastoparan was able to release cytochrome C in the cell line studied, indicating its potential use as an anticancer agent. Souza et al (2009) isolated two novel mastoparan peptides, Polybia-MP-II and Polybia-MP-III, from venom of Polybia paulista wasp, which exhibited hemolytic activity on erythrocytes. Also, Wang et al (2008) have reported that Polybia-MPI have anti-tumor activity.…”
Section: Waspmentioning
confidence: 99%